PENAMPILAN PRODUKSI SAPI PERAH FRIESIAN HOLSTEIN (FH) PADA BERBAGAI PARITAS DAN BULAN LAKTASI DI KETINGGIAN TEMPAT YANG BERBEDA - Aju Tjatur Nugroho K.; Puguh Surjowardojo; M. Nur Ihsan (Faculty of Animal Science, Universitas Brawijaya, 2010)
The aim of the research was to know the performance of milk yield Holstein Friesian (FH) of dairy cows at various parities and month of lactation in different altitude. The research was conducted from January to March 2010 at Setia Kawan dairy cooperative in Nongkojajar (highlands) and Suka Makmur dairy cooperative in Grati (lowlands). Both cooperatives were located in Pasuruan regency. The research materials used totally 90 heads of FH dairy cows (45 heads in Nongkojajar and 45 heads in Grati) which consisted of parity 2 (15 heads), parity 3 (15 heads) and parity 4 (15 heads). Each parity consisted of 2nd lactation (5 heads), 3rd lactation (5 heads) and 4th lactation (5 heads). The variables were daily milk yield, and environmental factors related to milk yield and reproductive performance of dairy cows that is temperature and air humidity, temperature humidity index (THI) and feed consumption. The method of the research was case study. The data had been analyzed by ANOVA and if there were significant influences it would be further tested using Duncan multiple range test. The results showed that the altitude significantly affected milk yield (P<0.05). Average milk yield at lowlands and highlands were 10.17±2.57 liters and 13.10±3.20 liters, but the 2nd, 3rd and 4th parities did not significantly affect milk yield. Another finding showed that the month of lactation significantly affected milk yield (P<0.05). Average milk yield in the 2nd, 3rd and 4th lactations were 12.98±3.61, 11.28±2.76 and 10.63±2.92 litters respectively. Based on the results it was concluded that the altitude and the month of lactation affected milk yield performances of FH dairy cows. It was suggested to improve environmental conditions at lowlands through controlling the temperature and humidity (THI) for not more than 72 so that appropriate for dairy cows and to improve management of productivity, reproductive and feeding practices. Keywords: milk yield, dairy cow, parity, month of lactation, altitude